Prominent Enlargement of the Facial Nerve Canal in a Case of a Persistent Stapedial Artery - Alexandra Libeert; Stefan Delrue; Marc Lemmerling (Journal of the Belgian Society of Radiology, 2024)
In this case report, we present a 23-year-old patient with complaints of a recurrent plop sound in the left ear. Non-contrast CT and MR imaging revealed an enlargement of the tympanic segment of the facial canal due to venous congestion. A persistent stapedial artery (PSA) and absent foramen spinosum were identified as concomitant factors. This unique combination of anomalies has not been previously reported and knowledge about this condition is essential to avoid unnecessary surgery. Teaching Point: A persistent stapedial artery may be associated with enlargement of the tympanic facial nerve canal due to venous congestion.